Consumption of dietary supplements to support weight reduction in adults according to sociodemographic background, body mass index, waist-hip ratio, body fat and physical activity - Adrian Lubowiecki-Vikuk; Magdalena Król-Zielińska; Adam Kantanista (BMC, 2019)
Abstract Background The aim of this study was to analyse the use of dietary supplements to support weight reduction (DSSWR) in adults according to sociodemographic background, body mass index (BMI), waist-hip ratio (WHR), body fat percentage (%BF) and level of physical activity (PA). Method Participants (n = 1130) were recruited from a region of Poland with a high rate of adult overweight and obesity. Based on anthropometric data, BMI and WHR were calculated. %BF was assessed using a bioimpedance method. To examine the association between DSSWR use and sociodemographic factors, BMI, WHR, %BF and PA multiple logistic regression were conducted. Results The rate of DSSWR use in the group studied was high (69.5%). A higher proportion of women, individuals aged 18-35 years, those who had completed higher education, those who did not report financial status as "poor", with a BMI < 18.5, normal %BF and individuals with a high level of PA used DSSWR. In complete case analysis (n = 1108), primarily financial status reported as "good" (OR = 2.18, 95% CI: 1.69, 2.81) or "hard to say" (OR = 2.41, 95% CI: 1.86, 3.12) (vs. "poor") and female sex (OR = 2.59, 95% CI: 2.17, 3.08) were associated with DSSWR intake. Conclusion It seems that primarily financial status and sex, but also age, education, and level of PA, have significance in DSSWR use in adults and may be considered when developing appropriate strategies for body weight management and health promotion.